Flow effects of central bank asset purchases on euro area sovereign bond yields: Evidence from a natural experiment - Roberto A. De Santis; Fédéric Holm-Hadulla (European Central Bank (ECB), 2017)
We estimate the response of euro area sovereign bond yields to purchase operations under the ECB's Public Sector Purchase Programme (PSPP), using granular data on all PSPP-eligible securities at daily frequency. To avoid simultaneity bias in the estimated relationship between yields and purchase volumes, we exploit a PSPP design feature that renders certain securities temporarily ineligible for reasons unrelated to their yields. Using these temporary purchase restrictions as an instrument to identify exogenous variation in purchase volumes, we find that the "flow effect" of PSPP operations has, on average, led to a temporary 7 basis-point decline in sovereign bond yields on the day of purchase. This impact estimate is well above those found in similar studies for the US; at the same time, our results imply that flow effects have accounted for only a limited share of the downward pressure of PSPP on sovereign yields, most of which instead derived from anticipation and announcement effects at the onset of the programme.
Keywords: E52; E58; E65; G12; 330; Quantitative Easing; Monetary Policy; Sovereign Yields; Natural Experiment